Reversible antifertility effect of Opuntia elatior Mill. fruit extract - MC, Ramya; ., Shivabasavaiah; T, Shivanandappa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was undertaken to evaluate the male antifertility potential of the fruit extract of O. elatior and its reversibility. Methods: The methanol fruit extract was administered orally (300, 900 mg/kg bw) to male rats for 60 days, and fertility was assessed by analysing spermatogenesis, epididymal sperm count, serum testosterone levels and testicular hydroxysteroid dehydrogenase activity. Fertility was assessed by mating treated rats with normally cycling virgin females. Reversibility of fertility suppression was studied by withdrawal of treatment for two weeks. Results: Epididymal sperm count and motility was markedly reduced up to 75-80% in rats treated for 60 days, without commensurate decline in serum testosterone levels. Testicular steroidogenesis was not affected as evident by the hydroxysteroid dehydrogenase activity. Fertility of the treated rats was suppressed when mated with normally cycling virgin female rats without affecting libido. The fertility suppression was dose-dependent being 100% in the highest dose. Withdrawal of the treatment for two weeks led to recovery of the epididymal sperm count, testicular HSDH activity, serum testosterone levels and the fertility. Conclusions: The methanol extract of the fruit of O. elatior shows reversible male antifertility activity without affecting the serum testosterone levels and libido.